Medycyna estetyczna – humanistyczne dążenie czy „enhancement”? - Napiwodzka-Bulek, Karolina (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
The aim of the paper is to consider the issue of modern aesthetic medicine considered as a humanism or, on the contrary, as human enhancement. The aim of enhancement is to improve and expand human possibilities in order to change their nature eventually. I present arguments for and against the thesis that aesthetic medicine might be considered as a typical humanistic aspiration for perfection. I pay close attention to the purpose criterion of medical practice by analyzing its therapeutic and aesthetic tasks.